Pendampingan Thaharah Tata Cara Mensucikan Najis Kepada Anak LKSA Darul Aitam Muslimat NU - Attamami, Shinta; Shilfi Alnannafsi Ima, Ardina; Nisa’ Nur , Fauziyatun; Nisa’ , Sa’adatun (LP3M IAIFA Kediri, 2024)
Thaharah assistance is an important practice in Islam related to the procedure of purifying uncleanness. Najis in this context refers to substances or objects that are considered unholy according to Islamic law. The process of purifying uncleanness involves certain steps that must be followed with care and cleanliness. thaharah assistance to the students can ensure that this procedure is carried out correctly by religious teachings. This study discusses various aspects of thaharah mentoring, including important stages in the process of cleansing unclean such as using clean water, staying away from contamination, and ensuring purity in the end. In addition, efforts to understand the philosophy and spiritual meaning behind this ordinance are also the main focus of this research. This study uses the PAR method or Participatory Action Research. Participatory Action Research is a research model that seeks something that connects the research process with the process of social change. Data was collected through direct observation and in-depth interviews with students and thaharah practitioners. The results of the study show that thaharah assistance is not just a physical process, but also has a deep psychological and spiritual dimension for the students.